2012
DOI: 10.1121/1.3662049
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional analyses of scattering by pressure-release sinusoidal surfaces

Abstract: Scattering by pressure-release sinusoidal surfaces in three dimensions is analyzed using the Fresnel phase approximation and realistic source and receiver directivity approximations. Geometrical shadowing and second-order scattering are explicitly included to explore the validity of the Kirchhoff approximation. No restrictions on the surface heights and slopes are made. The "goodness" of the resulting expressions is verified by requiring the pressure scattered by a sinusoidal surface to reduce to the image sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The resulting Fresnel expansions are given by (23) and (24) Substituting (23) and (24) into (7), and making the coordinate transformations given in (15) yields (25) Performing the and integrals gives a pair of Dirac delta functions (26) that allow the and integrals to be trivially evaluated to yield (27) In the narrowband case, the magnitude of the complex amplitude is given by , and when the time delay between hydrophones is steered to the image source the horizontal coherence in (27) reduces to (28) where . When the surface roughness goes to zero, both (20) and (28) reduce to the image solution [34], [35] for the acoustic intensity scattered by an omnidirectional CW source in the specular direction (29) This demonstrates the validity of the Fresnel phase approximation for an omnidirectional CW source; this is significant since the simplicity of the coherence expressions achieved in this paper relied on the use of the Fresnel phase approximation with the origin at the specular point. Finally, it also confirms that for an omnidirectional CW source the angles everywhere on the surface can be represented by their value at the origin without any loss in accuracy.…”
Section: Cross Correlation Of the Scattered Arrival At Two Horizonmentioning
confidence: 75%
See 3 more Smart Citations
“…The resulting Fresnel expansions are given by (23) and (24) Substituting (23) and (24) into (7), and making the coordinate transformations given in (15) yields (25) Performing the and integrals gives a pair of Dirac delta functions (26) that allow the and integrals to be trivially evaluated to yield (27) In the narrowband case, the magnitude of the complex amplitude is given by , and when the time delay between hydrophones is steered to the image source the horizontal coherence in (27) reduces to (28) where . When the surface roughness goes to zero, both (20) and (28) reduce to the image solution [34], [35] for the acoustic intensity scattered by an omnidirectional CW source in the specular direction (29) This demonstrates the validity of the Fresnel phase approximation for an omnidirectional CW source; this is significant since the simplicity of the coherence expressions achieved in this paper relied on the use of the Fresnel phase approximation with the origin at the specular point. Finally, it also confirms that for an omnidirectional CW source the angles everywhere on the surface can be represented by their value at the origin without any loss in accuracy.…”
Section: Cross Correlation Of the Scattered Arrival At Two Horizonmentioning
confidence: 75%
“…Here it will be assumed that the Kirchhoff approximation is valid when the surface slopes are not too steep. A recent study [35] showed that even for very steep slopes multiple scattering is insignificant at low to moderate grazing angles (below 60 ), and contributes to the scattered field only at very high grazing angles. At normal incidence the field due to multiple scattering was still 5-10 dB below the field due to single scattering.…”
Section: A the Kirchhoff Approximationmentioning
confidence: 97%
See 2 more Smart Citations
“…Our approach will be based on ray theory incorporated into the H-K integral. The benefit of this ray-based formulation is that it enables to correct geometric shadowing effects, 12 which are normally neglected in the Kirchhoff approximation along with multiple scattering effects.…”
Section: Introductionmentioning
confidence: 99%